Da Vinci robot-assisted laparoscopic retroperitoneal debridement for lumbar septic spondylodiscitis: A two-case report - Ye, Jichao; Liu, Hao; Hu, Xumin; Li, Jinteng; Gao, Liangbin; Tang, Yong (Frontiers in Surgery, 2022)
Anterior approach is one of the widely used surgical treatment for lumbar spondylodiscitis, but it has the disadvantages of large trauma and high incidence of complications. Our experiences suggested laparoscopic retroperitoneal approach could be effective to overcome those disadvantages of anterior approach. Herein, we report two cases of successfully treated lumbar pyogenic spondylodiscitis using robot-assisted laparoscopic retroperitoneal approach. The technique utilizes a robot that allows laparoscopic retroperitoneal approach while offering excellent high-definition images of three-dimensional vision. After the operation, both patients achieved well formation and fusion of the vertebrae. Preliminary evidence suggests that robot-assisted laparoscopic retroperitoneal approach may be feasible for the treatment of lumbar spondylodiscitis.